Effects of Gymnema lactiferum leaves on glycemic and lipidemic status in type 2 diabetic subjects - Thushari Bandara, Begum Rokeya, Sakina Khan, Liaquat Ali, Sagarika Ekanayake, Errol R. Jansz and Kandiah Balasubramanium (Bangladesh Pharmacological Society, 2009)
The diabetic patients in Sri Lanka use Gymnema lactiferum leaves as a treatment for diabetes. However, scientific data is not available on this plant. A clinical trial was conducted including 26, type 2 diabetic patients with hypercholesterolemia. The treatment group received a suspension of G. lactiferum leaf powder twice daily for four weeks. Blood parameters of both groups (treated and control) were determined at the beginning and the end of the study period. Study indicates significant effects on FBS (p=0.002), cholesterol (p=0.004), and LDL lowering (p=0.023) and a significant postprandial glucose lowering effect (p=0.026 for 60 min and p=0.022 for 120 min, after four weeks). In spite of the short study period, a significant reduction (p=0.012) in HbA1C levels was also observed.